Sensory analysis for cow milk product development using High Pressure Processing (HPP) in the dairy industry - Lim, Shu Huey; Chin, Nyuk Ling; Sulaiman, Alifdalino; Tay, Cheow Hwang; Wong, Tak Hiong (Multidisciplinary Digital Publishing Institute, 2022)
High pressure processing (HPP) can be applied as an alternative thermal treatment of milk to maintain its natural and original sensory quality. Milk was processed at 600 MPa for 10 min or given thermal treatment at 125 °C for 4 s. Sensory evaluation of treated milk samples was conducted using the triangle and the acceptance and preference tests. The triangle test was used as a discriminative test to check whether there was a noticeable difference between both treated milk samples. The acceptance and preference test determined attributes of milk including colour, milkiness, creaminess, mouthfeel, and aftertaste based on the 5-point just-about-right (JAR) scale. In the triangle test, 89.5% of panellists were able to identify the odd sample and differentiate milk processed using high pressure from heat treatment. For the acceptance and preference test, 61% of panellists gave higher overall preference for the high pressure processed milk over heat-treated milk. The JAR evaluation showed no significant differences (p > 0.05) in all evaluated milk attributes which included milkiness, creaminess, mouthfeel, and aftertaste, with the exception of colour. Overall, high pressure processed milk scored better in terms of organoleptic properties as the penalty value for most attributes including colour, milkiness, mouthfeel, and aftertaste were lower than the penalty of heat-treated milk, except for creaminess. Therefore, to improve the acceptance and preference of high pressure processed milk, future development needs to focus on increasing creaminess of high pressure processed milk.